THE EFFECT OF USING AUDIOVISUAL MEDIA ON STUDENTS’ SPEAKING ABILITY AT SMP NEGERI 1 BAUBAU - Baharudin Adu; Wa Ode Yesti Sari Zainuddin (English Education Journal, 2019)
This research was conducted to find out the significant effect of audiovisual media on students’ speaking ability. This research used a quasi-experimental design, and the sample of this research was class VIII.1 as an experimental class that consists of 22 students, and class VIII.12 as a control class with 22 students. The instrument of this research was a test, it was in the form of pre and post-test. The data analysis in this research was descriptive statistics and inferential statistics. The score of student’s basic speaking ability was calculated using Microsoft Excel 2010. The data resulted through that calculation was analyzed using the Statistical Package for Social Science (SPSS) 21.0 versions. The findings could be concluded that there was a significant effect of using Audio-Visual Media toward students’ speaking ability at second-grade students of SMP Negeri 1 Baubau. It can be seen based on the score of the t-test in the appendix, it showed that there was a significant effect on the students’ speaking ability in speaking. It was proved by the finding t-test (2.696) which was higher than ttable at 5% level of significance (2.04). It could be stated that 2.04<2.696 for students’ speaking ability. It meant that the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. In conclusion, teaching speaking by using Audio Visual at the second-grade students of SMP Negeri 1 Baubau better than without using Audio-Visual Media.